DEVELOPING ELT MATERIALS: THE KEY TO FOSTERING EFFECTIVE INSTRUCTION OF READING COMPARISON AND CONTRAST TEXTS - Ive Emaliana; Tania Wahyuvi Amaranggani (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2020)
Reading comparison and contrast texts in English language teaching (ELT) program was developed which ensured a range of students could be facilitated with instructional materials for their course and level of study. These materials have been developed around the concept of educational inclusion, intercultural communication and information and communication technology (ICT) utilization which can be combined into whole units of learning (topics), teaching and learning activities and media, and ultimately a student book, student work book, and lecturer guide. On the basis of the underlying philosophy from the new curriculum of the study program, we considered effective instruction to be a key element in engaging students with reading materials. There were six stages of R&D method from Borg and Gall (2003) modified by the researchers consist of need analysis, developing material, expert validation, revision, try out, and the final product. Three instruments consist of informal interview, expert’s validation checklist, and questionnaire for the product try out were utilized to develop reading comprehension instructional materials. The products consisted of student book chapter, student workbook chapter, and lecturer manual book chapter of reading comparison, and contrast texts. In consequence, the key aim of this development was to stimulate and engage students, fostering better involvement with the reading comprehension materials and hence better learning.